Fiscal policy challenges in oil-exporting countries – a review of key issues - Michael Sturm; François Gurtner; Juan Gonzalez Alegre (European Central Bank (ECB), 2009)
Fiscal policy choices have a particularly significant impact on economic performance in oil-exporting countries, owing to the importance of the oil sector in the economy and the fact that in most countries oil revenues accrue to the government. At the same time, fiscal policy in oil-centred economies s facing specific challenges, both in the long run, as regards intergenerational equity and fiscal sustainability, and in the short run, as regards macroeconomic stabilisation and fiscal planning. Institutional responses to the specific fiscal challenges in oil-exporting countries involve conservative oil price assumptions in the budget, the establishment of oil stabilisation and savings funds and fiscal rules. Fiscal policy in most oil-exporting countries has been expansionary over the past years in the wake of high oil prices. Fiscal expansion has added to inflationary pressure, and monetary policy has been constrained in tackling inflation as a result of prevailing exchange rate regimes. While, in this context, fiscal policy is the major tool for macroeconomic stabilisation, it has faced competing objectives and considerations. Cyclical considerations would have warranted fiscal restraint, but, in times of high oil prices, pressures to increase public spending have been mounting. Such pressures stem from primarily distribution-related considerations, development-related spending needs (e.g. in the areas of physical and social infrastructure) and international considerations in the context of, for example, global imbalances. The sharp fall in oil prices since mid-2008 has brought to the fore a different question – whether oil exporters can sustain spending levels reached in previous years.
Keywords: E62; E63; H30; H60; Q32; Q38; 330; Fiscal policy; oil-exporting countries; inflation; global imbalances.